Crença no mundo justo e ditados populares - Linhares, Layanne Vieira (2017)
This work is part of the study about Belief in a Just World (BJW) and discrimination, with two main objectives: a) to investigate BJW’s moderating role in discrimination against homosexuals and b) to develop a BJW’s scale that has psychometric parameters most suitable to Brazil, using popular sayings. For this porpuse, three studies were carried out. In the two initial studies (N = 177; N = 122), which formed the first article of this dissertation, was developed a new instrument of BJW. Together, the results indicated a one-way solution, with an internal consistency of 0.78, as well as a positive correlation with other CMJ scales validated in Brazil and significant indexes, indicating the power of the new scale to predict secondary victimization, showing satisfactory indexes. The third study (N = 295), which is part of the second article, investigated discrimination against male homosexuals with AIDS and the influence of BJW on the attribution of responsibility for their disease. The results indicated that the isolated effects of sexual orientation and type of disease were significant, revealing that individuals with AIDS were assigned more responsibility than those with lung cancer, as well as homosexuals were more blamed than heterosexuals. The isolated effect of BJW was not significant. The results of moderation have indicated that BJW plays a moderating role in attributing responsibility, revealing that participants with high adherence to BJW have blamed more the homosexuals and patients with AIDS.